2021
DOI: 10.1109/access.2021.3072731
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram-Based Attention Level Classification Using Convolution Attention Memory Neural Network

Abstract: Attentive learning is an important feature of the learning process. It provides a beneficial learning experience and plays a key role in generating positive learning outcomes. Most studies widely applied electroencephalogram (EEG) to measure human attention level. Although most studies use EEG handcrafted features and statistical methods to classify attention level, a more effective feature learning technique is still needed. In this paper, we aim to analyze participants' EEG signals through a deep learning mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Different approaches like SVM, K-nearest neighbour (KNN), and neuro-fuzzy have been utilized for classification purposes, and the authors found the maximum accuracy with the SVM classifier of 96.70%. Toa et al [69] proposed a method to detect the attention level, i.e., whether the subject is attentive or inattentive. The proposed convolution attention memory network (CAMNN) model outperforms to the previously used method with an accuracy of 92%.…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches like SVM, K-nearest neighbour (KNN), and neuro-fuzzy have been utilized for classification purposes, and the authors found the maximum accuracy with the SVM classifier of 96.70%. Toa et al [69] proposed a method to detect the attention level, i.e., whether the subject is attentive or inattentive. The proposed convolution attention memory network (CAMNN) model outperforms to the previously used method with an accuracy of 92%.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the classification accuracy was 73.3% and the gamma 1 wave can be used to identify the confusion [23]. A deep learning approach can also be implemented on EEG signals to find out the attention level of a student [33]. Thus, the survey concludes that the traditional machine learning, deep learning and spiking neural network analysed and classified the EEG signals for extracting specific patterns [27,28].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, the deep learning-based system is suggested by a researcher on the application such as lung cancer (K.-L. , (Kumar et al, 2015), breast cancer classification (D. Wang et al, 2016), (Fung Fung Ting et al, 2019), cognitive classification (Toa et al, 2021), Alzheimer's disease (AD) (Ji et al, 2019), (Suk et al, 2014), and even pain quantification (Elsayed et al, 2020). Moreover, recent studies mention that deeply learned features can provide a more effective feature learning technique for image classification compared to handcrafted features (Toa et al, 2021), (Arevalo et al, 2016). A. Cruz-Roa et al provide automatic detection of IDC in WSI using CNN.…”
Section: Deep Learning In Image Classificationmentioning
confidence: 99%